Health and Wellness Centres: Expanding Access to Comprehensive Primary Health Care in India - Nirupam Bajpai; Manisha Wadhwa (Columbia University, Earth Institute, Center for Sustainable Development (CSD), 2019)
India's achievements in the field of health leave much to be desired and the burden of disease among the Indian population remains high. Infant and child mortality and morbidity and maternal mortality and morbidity affect millions of children and women. IMR at 37 per 1,000 live births and MMR at 130 per 100,000 live births are high by international standards, and life expectancy at around 68 years is much lower than in China, other countries in East Asia, and the advanced economies. Fertility rates are still very high, and the population continues to grow rapidly, pressing hard on India's fragile ecosystems and natural environment. Several infectious diseases are re-emerging as epidemics. Many of these illnesses and deaths can be prevented and/or treated cost-effectively with primary health care services provided by the public health system. An extensive primary healthcare infrastructure provided by the government exists in India. Yet, it is inadequate in terms of coverage of the population, especially in rural areas, and grossly underutilized because of the dismal quality of healthcare being provided. In most public health centers which provide primary healthcare services, drugs and equipment are missing or in short supply, there is shortage of staff and the system is characterized by endemic absenteeism on the part of medical personnel due to lack of control and oversight. As a result, most people in India, even the poor, choose expensive healthcare services provided by the largely unregulated private sector. Not only do the poor face the double burden of poverty and illhealth, the financial burden of ill health can push even the non-poor into poverty. Among the 50 lowmiddle income group nations, India is the 6th biggest out-of-pocket spender. The household out-ofpocket expenditure accounts for 67 percent of the total health expenditure. Last year, the Government of India embarked on a path to achieve Universal Health Coverage for all the citizens of India. In the Union budget 2017-18, the government announced the Ayushman Bharat Yojana, comprising of two major initiatives - the National Health Protection Scheme and the Health and Wellness Centres (HWCs). The present paper gives a detailed account of the Health and Wellness Centres Initiative under Ayushman Bharat Yojana launched by the government. The role of Information and Communications Technology (ICT) in the delivery of comprehensive primary health care through HWCs is examined. Further, the areas of opportunities and key challenges related to the Health and Wellness Centres Initiative is discussed in detail.
Keywords: 330; Health and Wellness Centres; Ayushman Bharat; Information and Communications Technology; ICT; India